HUBUNGAN KEMAMPUAN MENYELESAIKAAN TUGAS- TUGAS PELAJARAN DENGAN HASIL BELAJAR SISWA - Suryadi S; Mori Dianto; Besti Nora Dwi Putri (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
Student learning outcomes can be influenced by the ability of students tocomplete lesson assignments. The phenomenon in the field some students are not able to complete the task assignments given by the teacher. The research aims to reveal how the relationship between the ability to complete task assignments with student learning outcomes. Using quantitative methods with the type of correlational research. The study population was 384 middle school students. The  sampling technique is Proportional Random Sampling with a sample of 78 people.Data analysis techniques used the Pearson Product Moment formula with the help of the Statistical Product and Service Solution for windows release 17.0 program. The research findings show that (1) the ability to complete the task assignments in junior high is in the good category, (2) the learning outcomes of students in junior high are in the good category. (3) There is a significant relationship between the ability to complete lesson tasks with the Pearson correlation student learning outcomes of 0.416 and a significance level of 0.000, with a sufficient level ofrelationship.Keywords: Skills Completing Tasks, Learning Outcomes